2020
DOI: 10.48550/arxiv.2010.00012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An ALMA survey of $λ$ Orionis disks: from supernovae to planet formation

Megan Ansdell,
Thomas J. Haworth,
Jonathan P. Williams
et al.

Abstract: Protoplanetary disk surveys by the Atacama Large Millimeter/sub-millimeter Array (ALMA) are now probing a range of environmental conditions, from low-mass star-forming regions like Lupus to massive OB clusters like σ Orionis. Here we conduct an ALMA survey of protoplanetary disks in λ Orionis, a ∼5 Myr old OB cluster in Orion, with dust mass sensitivities comparable to the surveys of nearby regions (∼0.4 M ⊕ ). We assess how massive OB stars impact planet formation, in particular from the supernova that may ha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 110 publications
(179 reference statements)
1
2
0
Order By: Relevance
“…Previous studies show several important steps in disk evolution in the protoplanetary disk phase: the mean millimeter dust mass of the disks decreases with the age of the star-forming region, with a stronger decrease for low-mass stars (Ansdell et al 2017); the dust disk radius decreases with age (Hendler et al 2020); the number of disks in a star-forming region drops with age, both according to infrared excess and number of accreting stars (Hernández et al 2007;Fedele et al 2010;Ribas et al 2014); accretion rates remain high even for older stars (Rugel et al 2018;Venuti et al 2019;Manara et al 2020), which are consistent with viscous evolution models when a low viscosity of α v 1 = 10 −3 is assumed, in combination with dust evolution (Sellek et al 2020a); millimeter dust masses of non-accreting young stars (WTTS) and debris disks are well below those of protoplanetary disks (Wyatt 2008;Panić et al 2013;Hardy et al 2015). Interestingly, several older star-forming regions contain one to a few bright, massive disks which lie well above the mean dust mass in that region (Ansdell et al 2015(Ansdell et al , 2020, and, lastly, transition disks with large inner dust cavities have been suggested to be outliers in the general disk distribution (Owen & Clarke 2012;van der Marel et al 2018), perhaps following a separate evolutionary path (van der Marel & Mulders, subm. ).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies show several important steps in disk evolution in the protoplanetary disk phase: the mean millimeter dust mass of the disks decreases with the age of the star-forming region, with a stronger decrease for low-mass stars (Ansdell et al 2017); the dust disk radius decreases with age (Hendler et al 2020); the number of disks in a star-forming region drops with age, both according to infrared excess and number of accreting stars (Hernández et al 2007;Fedele et al 2010;Ribas et al 2014); accretion rates remain high even for older stars (Rugel et al 2018;Venuti et al 2019;Manara et al 2020), which are consistent with viscous evolution models when a low viscosity of α v 1 = 10 −3 is assumed, in combination with dust evolution (Sellek et al 2020a); millimeter dust masses of non-accreting young stars (WTTS) and debris disks are well below those of protoplanetary disks (Wyatt 2008;Panić et al 2013;Hardy et al 2015). Interestingly, several older star-forming regions contain one to a few bright, massive disks which lie well above the mean dust mass in that region (Ansdell et al 2015(Ansdell et al , 2020, and, lastly, transition disks with large inner dust cavities have been suggested to be outliers in the general disk distribution (Owen & Clarke 2012;van der Marel et al 2018), perhaps following a separate evolutionary path (van der Marel & Mulders, subm. ).…”
Section: Introductionsupporting
confidence: 77%
“…The decrease in M dust with L fract in the Class II phase as discussed in Section 5.1 caused by radial drift does not appear to affect the structured disks: whereas the majority of the dust masses in Upper Sco disks lie well below those of Lupus, the structured disks' M dust values are similar between these two regions. The structured disks appear to follow an alternate evolutionary track with a delayed decrease in M dust similar to the outlier disks from Ansdell et al (2020). Dust traps prevent these disks from undergoing radial drift-dominated mm-dust evolution while the µm-sized dust is still being gradually dissipated, thus they retain their high dust mass (Pinilla et al 2020;Sellek et al 2020a, van der Marel & Mulders, subm.).…”
Section: Ring and Transition Disksmentioning
confidence: 88%
“…Vicente & Alves 2005;Eisner & Carpenter 2006;Mann et al 2014), the Orion Nebula Cluster (e.g. Mann & Williams 2010;Eisner et al 2018), Cygnus OB2 (Guarcello et al 2016), NGC 1977(Kim et al 2016, NGC 2244 (Balog et al 2007), Pismis 24 (Fang et al 2012), NGC 2024(van Terwisga et al 2020, 𝜎 Orionis (Ansdell et al 2017), and 𝜆 Orionis (Ansdell et al 2020). Younger and low-mass star-forming regions such as Lupus, Taurus, Ophiuchus, and the Orion Molecular Cloud 2 tend to have higher average disc masses than denser regions such as the Orion Nebula Cluster (Eisner et al 2008;Ansdell et al 2016;Eisner et al 2018;van Terwisga et al 2019).…”
Section: Introductionmentioning
confidence: 99%